Genome Assembly and Analyses of the Macrofungus Macrocybe gigantea. (19th January 2021) - Kui, Ling; Zhang, Zhe; Wang, Yangzi; Zhang, Yesheng; Li, Shiming; Dong, Xiao; Xia, Qiuju; Sheng, Jun; Wang, Jian; Dong, Yang
Abstract : Macrocybe gigantea ( M. gigantea ) is a macrofungus genus that contains a big number of fairly fleshy gilled mushrooms with white spores. This macrofungus produces diverse bioactive compounds, antioxidants, and water-soluble polysaccharides. However, the genomic resources of this species remain unknown. Here, we assembled the genome of M. gigantea (41.23 Mb) into 336 scaffolds with a N50 size of 374, 455 bp and compared it with the genomes of eleven other macrofungi. Comparative genomics study confirmed that M. gigantea belonged to the Macrocybe genus, a stand-alone genus different from the Tricholoma genus. In addition, we found that glycosyl hydrolase family 28 (GH28) in M. gigantea shared conserved motifs that were significantly different from their counterparts in Tricholoma . The genomic resource uncovered by this study will enhance our understanding of fungi biology, especially the differences in their growth rates and energy metabolism.